Pengaruh Teknik Relaksasi Terhadap Pengurangan Nyeri Persalinan Pada Ibu Primigravida - Rubiah R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Labor pain is a physiological experience felt by almost all mothers giving birth, especially primigravida mothers who have no previous experience of childbirth. Uncontrolled labor pain can increase anxiety, fatigue, and hinder the progress of labor. One non-pharmacological method that can be used to reduce labor pain is relaxation techniques, which aim to help mothers control their physical and psychological responses to pain. Objective: This study aims to determine the effect of relaxation techniques on reducing labor pain in primigravida mothers. Method: This study used a quantitative design with a pretest–posttest quasi-experimental approach. The study sample consisted of 30 primigravida mothers who underwent stage I labor in the delivery room of Health Center/Hospital X, selected using purposive sampling. The level of labor pain was measured using a numeric rating scale (NRS) before and after the administration of relaxation techniques. Data analysis was performed using a paired t-test with a significance level of α = 0.05. Results: The results showed a significant decrease in labor pain levels in primigravida mothers after being given relaxation techniques, with a p-value < 0.05. Conclusion: Relaxation techniques have a significant effect on reducing labor pain in primigravida mothers. These techniques can be used as safe and effective nonpharmacological interventions in midwifery care.